(untitled) (PETITUM, 2026)
This study aims to analyze the legal provisions governing the termination of investigations in the Indonesian criminal justice system and to evaluate their implementation in ensuring legal certainty for the parties involved. The research focuses on the termination of an investigation (SP3) related to an alleged property damage case reported by Jimmy as the complainant. The research examines three main aspects: the legal basis for terminating the investigation, the decision-making process, and the legal implications for the complainant and the suspect. This research uses a normative legal method with a qualitative approach by examining the Indonesian Criminal Procedure Code (KUHAP), the Regulation of the Chief of Police Number 6 of 2019, and relevant legal literature. The results indicate that the termination of the investigation in this case was not carried out in accordance with applicable legal and procedural standards. The investigators did not provide an objective explanation regarding the legal basis for the termination, there was a lack of transparency in the evaluation of evidence, and no indication of the prosecutor’s involvement as the case controller. Moreover, important documents such as the investigation summary and SP2HP were not provided to the complainant, resulting in legal uncertainty and potentially weakening public trust in law enforcement institutions.